CA125 suppresses amatuximab immune-effector function and elevated serum levels are associated with reduced clinical response in first line mesothelioma patients. Issue 7 (3rd July 2018) - Nicolaides, Nicholas C.; Schweizer, Charles; Somers, Elizabeth B.; Wang, Wenquan; Fernando, Shawn; Ross, Erin N.; Grasso, Luigi; Hassan, Raffit; Kline, J. Bradford
ABSTRACT: The tumor-shed antigen CA125 has recently been found to bind certain monoclonal antibodies (mAbs) and suppress immune-effector mediated killing through perturbation of the Fc domain with CD16a and CD32a Fc-γ activating receptors on immune-effector cells. Amatuximab is a mAb targeting mesothelin whose mechanism of action utilizes in part antibody-dependent cellular cytotoxicity (ADCC). It is being tested for its therapeutic activity in patients with mesothelioma in combination with first line standard-of-care. To determine if CA125 has immunosuppressive effects on amatuximab ADCC and associated clinical outcomes, post hoc subgroup analysis of patients from a Phase 2 study with primary diagnosed stage III/IV unresectable mesothelioma treated with amatuximab plus cisplatin and pemetrexed were conducted. Analysis found patients with baseline CA125 levels no greater than 57 U/m (∼3X the upper limit of normal) had a 2 month improvement in progression free survival (HR = 0.43, p = 0.0062) and a 7 month improvement in overall survival (HR = 0.40, p = 0.0022) as compared to those with CA125 above 57 U/mL. In vitro studies found that CA125 was able to bind amatuximab and perturb ADCC activity via decreased Fc-γ-receptor engagement. These data suggest that clinical trial designs of antibody-based drugs in cancers producing CA125, including mesothelioma, should consider stratifying patients on baseline CA125 levels for mAbs that are experimentally determined to be bound by CA125.